Gossip and Hidden Transcript in The Online and Offline Interaction: The Case of Closed Group Communication - Rudi Sukandar (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2017)
Despite having negative content, gossip and backstage talks can also be a medium to learn about differences and provide information for the rest of the community. Furthermore, backstage talks not only contain mere gossip, but also reflect the hidden transcripts by individuals who perceived themselves to be less powerful than the power holders. Given the phenomena, this paper attempted to investigate the online backstage talks between community members and their face-to-face interaction with the object of their gossips by using the concepts of Goffman’s dramaturgy, gossip, and hidden transcript. The study found that Goffman’s (1959) concept of performance, while useful, could not fully work in analyzing deviant behaviors. This study further confirms Wittek and Wielers’ (1998) affirmation that coalition triads as the best predictors of gossip behavior. However, another triad model, called neutralization, is proposed to predict the occurrences of gossip. Finally, the study also confirms the existence of the hidden transcripts by community participants who felt being oppressed by the powers that be.